Mastering Solidworks / Matt Lombard. - Lombard, Matt (Sybex, 2019)
'Mastering SolidWorks' is the reference-tutorial for all users Packed with step-by-step instructions, video tutorials for over 40 chapters, and coverage of little-known techniques, this book takes you from novice to power user with clear instruction that goes beyond the basics.